Towards effective realisation of the right to a satisfactory environment in the African Charter on Human and Peoples' Rights: a case for domestic horizontal application - Cistac, Doutor Gilles (University of Pretoria, 2006)
Mini Dissertation (LLM)--University of Pretoria, 2006.